2017
DOI: 10.1002/mp.12161
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Determination of individual thyroid clearance effective half-life with a common handheld electronic dosimeter

Abstract: Purpose: To determine the thyroid clearance effective half-life with a common handheld electronic dosimeter (ED) in patients undergoing radioiodine treatment for hyperthyroidism.Methods: Dose rates from twelve inpatients were measured daily with an ED and with a clinical uptake counter. The ED was attached to the patient with two different setups, one using a cervical collar and another employing a neck strap. Estimation of was performed by linear regression analysis of the log of both the ED and the uptake co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It is commonly known that short Teff increases the risk for RIT failure, so it is crucial for GD patients intended to receive RIT therapy to determine Teff before RIT [ 16 ]. However, it is inconvenient to determine Teff directly, which demands 131 I uptake measurements at 24 hours, 48 hours, and 4-6 days, requiring no less than five patient visits over a 5-7 day period, and some authors suggested that up to 10 measurements over a 7-day period are required [ 14 , 15 ]. Based on this, we investigated the factors that could be used to predict Teff and further developed a Teff prediction model in our patient population, which was confirmed to be used more conveniently and practically for our routine work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly known that short Teff increases the risk for RIT failure, so it is crucial for GD patients intended to receive RIT therapy to determine Teff before RIT [ 16 ]. However, it is inconvenient to determine Teff directly, which demands 131 I uptake measurements at 24 hours, 48 hours, and 4-6 days, requiring no less than five patient visits over a 5-7 day period, and some authors suggested that up to 10 measurements over a 7-day period are required [ 14 , 15 ]. Based on this, we investigated the factors that could be used to predict Teff and further developed a Teff prediction model in our patient population, which was confirmed to be used more conveniently and practically for our routine work.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly known that short Teff increases the risk for RIT failure, therefore, it is crucial for GD patients intended to receive RIT therapy to determine Teff. However, it is often argued that determining Teff is laborious, which requires no less than five patient visits over a 5-7 day period– this makes a novel, highly accurate Teff prediction model very valuable [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each module is connected to the data acquisition unit and contains a scintillation detector (3 mm × 3 mm active detection surface) faced to the body surface. The use of a comparable device was recently explored by Fürstner et al Example photos of the CoTI are shown in Fig. .…”
Section: Methodsmentioning
confidence: 99%